Channel Resource Allocation for VoIP Applications in Collaborative IEEE 802.11/802.16 Networks - Foh ChuanHeng; Cai Jianfei; Gao Deyun; Zhang Hongke (EURASIP Journal on Wireless Communications and Networking, 2010)
Collaborations between the IEEE 802.11 and the IEEE 802.16 networks operating in a common spectrum offers dynamic allocate bandwidth resources to achieve improved performance for network applications. This paper studies the bandwidth resource allocation of collaborative IEEE 802.11 and IEEE 802.16 networks. Consider delivering data packets between mobile stations and Internet users through an access point (AP) of the IEEE 802.11 network and a base station (BS) of the IEEE 802.16 network operating on a common frequency band, we analyze their medium access control (MAC) protocols, frame structures, and design a cooperation mechanism for the IEEE 802.11 and the IEEE 802.16 networks to share the same medium with adaptive resource allocation. Based on the mechanism, an optimized resource allocation scheme is proposed for VoIP applications. An analytical model is developed for the study to show significant improvements in voice capacity for our optimized resource allocation scheme.